2012
DOI: 10.1118/1.4770285
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of superficial dosimetry between treatment planning system and measurement for several breast cancer treatment techniques

Abstract: In general, TPS even with advanced algorithms do not provide accurate dosimetry in the buildup region, as verified by EBT2 film for all treatment techniques. For all cases, TPS and measured doses were in agreement from 6 mm in depth but differed at shallower depths. Grid size plays an important role in dose calculation. For accurate dosimetry small grid size should be used where differences are lower between TPS and measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…These values are in good agreement with our calculated results. Without correction, the surface dose is 23.5% higher, which is in agreement with the results of Akino et al (11) and Polednik et al (12) …”
Section: Discussionsupporting
confidence: 92%
“…These values are in good agreement with our calculated results. Without correction, the surface dose is 23.5% higher, which is in agreement with the results of Akino et al (11) and Polednik et al (12) …”
Section: Discussionsupporting
confidence: 92%
“…Moreover, differences may be explained by the uncertainties of calculation in the first mm. Indeed, TPS with collapsed cone algorithms, do not provide accurate dosimetry in the first millimeters 26, 27, 28. As stated in the AAPM TG 176 report, the depth of the sensitive basal layer ranges from 0.05 to 0.4 mm deep 29, 30.…”
Section: Discussionmentioning
confidence: 99%
“…This is to be expected because AXB handles interfaces and inhomogeneities more accurately than AAA 13, 24. AAA has been shown to be agree more closely with MC calculations than older algorithms,25 though AAA is not sufficiently accurate for performing superficial dosimetry 26. Superficial dose is not commonly assessed using an evaluation volume; however, we have found that upon implementation of AXB for breast, physicians, and dosimetrists can expect to see higher overall superficial doses than when using AAA.…”
Section: Discussionmentioning
confidence: 78%